2017
DOI: 10.3892/mmr.2017.6461
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Wnt/β-catenin signaling pathway in inducing apoptosis and renal fibrosis in 5/6-nephrectomized rats

Abstract: Renal fibrosis is the final common pathway of all progressive renal disease. Excessive and chronic activation of the Wnt/β-catenin signaling pathway results in chronic kidney disease (CKD) progression. To mimic CKD, the present study used 5/6-nephrectomized rats, and alterations in kidney histology, expression of β-catenin and renal cell apoptosis were assessed. In addition, mesangial cells were cultured in vitro and transfected with β-catenin siRNA to evaluate the effect of blocking Wnt/β-catenin signaling on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 31 publications
(30 reference statements)
1
25
0
Order By: Relevance
“…Given the vital role of myofibroblast proliferation in resveratrol‐mediated anti‐fibrosis, we speculated that proliferation‐related pathways likely participate in fibrogenesis. Previous studies have revealed that the MAPK, PI3K/Akt, JAK2/STAT3, and Wnt/β‐catenin signalling pathways are involved in renal fibrosis (Ai et al, ; Gao et al, ; Lin et al, ; Wang, Wang, et al, ; Wang, Zhou, et al, ). In this study, the activities of MAPK (Figure a), PI3K/Akt (Figure b), JAK2/STAT3 (Figure c), and Wnt/β‐catenin (Figure d) in the UUO group were enhanced compared with those in the sham‐operated group, indicating that activated signal transduction was involved in the proliferation and transdifferentiation of myofibroblasts.…”
Section: Resultsmentioning
confidence: 99%
“…Given the vital role of myofibroblast proliferation in resveratrol‐mediated anti‐fibrosis, we speculated that proliferation‐related pathways likely participate in fibrogenesis. Previous studies have revealed that the MAPK, PI3K/Akt, JAK2/STAT3, and Wnt/β‐catenin signalling pathways are involved in renal fibrosis (Ai et al, ; Gao et al, ; Lin et al, ; Wang, Wang, et al, ; Wang, Zhou, et al, ). In this study, the activities of MAPK (Figure a), PI3K/Akt (Figure b), JAK2/STAT3 (Figure c), and Wnt/β‐catenin (Figure d) in the UUO group were enhanced compared with those in the sham‐operated group, indicating that activated signal transduction was involved in the proliferation and transdifferentiation of myofibroblasts.…”
Section: Resultsmentioning
confidence: 99%
“…Two important features of CKD, inflammation and oxidative stress, can drive the progression of CKD and lead to cardiovascular and other body system complications [6,7]. Moreover, another key feature of CKD is renal fibrosis, which is the final pathological stage of all progressive renal diseases [8,9]. As a model of CKD, 5/6 nephrectomized (5/6Nx) rats have been frequently used as to study the progression of CKD [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Cisternas et al discussed the pro-brotic effect of Wnt signaling in both skeletal muscle and kidney [33]. Mounting evidence established that the Wnt/β-catenin signaling pathway plays a crucial role in regulating the development and progression of renal brotic lesions following injury [34][35][36]. The Wnt/β-catenin signal is relatively silent in the kidneys of healthy adults and is activated once the kidneys are subjected to various kinds of damages [37].…”
Section: Discussionmentioning
confidence: 99%